Verification of ANSYS CFX software package for numerical analysis of three-dimensional viscous flow in the compressor - Шелковский, Михаил Юрьевич (Eastern-European Journal of Enterprise Technologies, 2012)
Settlement pilot study of a three-dimensional viscous current in a flowing part of flat compressor lattices of profiles, devyatistupen-chaty KND of stationary GTD on the basis of ANSYS CFX. Choice of models of turbulence, processes and designs.